Implementasi E-Modul pada Program Studi Manajemen Informatika Universitas Bina Darma Berbasis Web Mobile - Imam Solikin (Ikatan Ahli Informatika Indonesia (IAII), 2018)
The Information Management Studies Program is a Diploma (D III) education, which is on the Vocational Faculty. In the process of lectures are still many who use the module (paper print module). Situations like this resulted in students less than the maximum in learning and less to understand the subject matter because there is material that is missed, thus resulting in knowledge of students will less than the maximum science. One solution of the problem, the need for development in lecturing process by adding electronic media such as e-module. E-module is a document or article in electronic format. This research implements information technology (IT) in the form of e-module to improve student study Program Management Informatics Faculty Vocational University Bina Darma. The purpose of this implementation in order to facilitate student learning wherever the place because it can be accessed and learned by using smarthpone online in the form of e-module is a full module from the first material to the end. Development method used in this research is linear sequential model with several stages that is analysis, design, coding, testing, and support. The results obtained from the research in the form of mobile web-based e-module applications that can be opened through a smartphone. With this e-module student learning process can be more effective.